Impact through versatility: Patterns of in vivo dosimetry utilization with TLD across a large multi-site radiotherapy department - Lonski, Peta; Kron, Tomas (Frontiers in Oncology, 2022)
The complexity of modern radiotherapy treatment pathways necessitate input from different professions to ensure treatment is delivered safely and as planned. In vivo dosimetry is one method of treatment verification providing the opportunity for both in-field verification or out-of-field measurements. It was the aim of this work to review the impact of an in vivo dosimetry programme with the view to justify resources and assist in developing a plan for equipment acquisition. Results of 310 (approximately 2 per 1000 treatment fractions) in vivo measurements were reviewed over a two-year time span. The in vivo dosimetry programme using thermoluminescence (TLD) chips was able to detect three significant treatment errors, amongst some 13 000 patients treated. These errors would likely to have been undetected through other quality assurance measures. Increasing demands in workload were found to be associated with commissioning of new equipment and techniques. A skilled operator with knowledge of TLD physics, treatment planning system (TPS) dose calculation algorithms and radiation transport proved to be essential for appropriate interpretation of TLD results particularly in complex radiation delivery scenarios. TLD continues to play a large role in patient safety and quality assurance at our institution.